TACKLING ANOREXIA: CURRENT TRENDS AND INNOVATIONS IN TREATMENT STRATEGIES - Martyna Bukowiec; Klaudia Korona; Magdalena Gąsior; Jagoda Rogowska; Michał Kopera (International Journal of Innovative Technologies in Social Science, 2025)
Anorexia nervosa is a severe psychiatric disorder characterized by persistent food restriction, distorted body image, and an intense fear of weight gain. It exhibits one of the highest mortality rates among mental illnesses, second only to opioid use disorder. This review synthesizes current evidence on the etiology, diagnosis, comorbidities, and treatment of anorexia nervosa. The multifactorial pathogenesis includes genetic, neurobiological, psychological, and sociocultural components. Diagnostic criteria according to ICD-11 emphasize low body weight and behavioral patterns of restrictive eating. anorexia nervosa frequently coexists with medical complications affecting cardiovascular, gastrointestinal, endocrine, and skeletal systems, which contribute to its high morbidity and mortality. The review evaluates established psychological treatments, and family-based therapy, and highlights the limited and effectiveness of pharmacotherapy, including antidepressants and antipsychotics. Emerging treatments ranging from intranasal oxytocin, cannabinoids, and ketamine to neuromodulatory methods like repetitive transcranial magnetic stimulation and virtual reality therapy show promise, but require further validation. The paper also explores inpatient care, alternative therapies (acupuncture, electroconvulsive therapy), and interventions targeting complications such as bone density loss. Despite significant advancements, relapse rates remain high, and recovery is often incomplete, underscoring the urgent need for individualized, multidisciplinary treatment approaches and further research into mechanism-based and integrative therapies.